ANALYSIS OF THE DIFFICULTIES OF ELEMENTARY SCHOOL TEACHERS IN IMPLEMENTING THE VALUE OF CHARACTER EDUCATION IN SDN 3 KAYANGAN - Revia Esperanza; Lalu Hamdian Affandi; Baiq Niswatul Khair (PROGRES PENDIDIKAN, 2022)
This study aims to determine the difficulties of elementary school teacher in planning, to implement, evaluate the ingculcation of character values in studies and to determine the difficulties of elementary instilling character values of caring for a disciplined and friendly environment in students. This type of reseaech is descriptive qualitative. The subjects of this study were teacher of grades I, II, IV and V SDN 3 Kayangan. data collection techniques were carried out through observation and interviews. The result of this study show that 1) The difficulty of teacher in planning the cultivation of character values show that 80% of teacher at SDN 3 Kayangan do not understand to plan the culvation of character values in studens. 2) The difficulty of teacher in implementing character value planting show that 60% of SDN 3 Kayangan teachers do not understand the varios strategies that can be used in instilling character value in students. 3) The difficulty of teacher in evaluating the character values of students show that 80% of the teacher at SDN 3 Kayangan do not understand how to do the evaluation of character values in students. The difficulty of teacher of maintaining cleanliness, the difficulty of teacher in instilling the value of discipline is that there are still many students who do not obey the rules, The difficulty of teacher in instilling friendly values is for low students who mock their friends with words that are not polite, and are still who from gangs to play.